Analisis Minat pada Pembiayaan Murabahah Bank Syariah Indonesia : Studi Pedagang Pasar Senin Desa Petaling Jaya - Ayu Uswatun Hasanah; Ahmad Syahrizal; Saijun Saijun (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This paper discusses the interest of traders from one of Bank Syariah Indonesia's products in providing business capital or other uses to traders in Pasar Senen Petaling Jaya. This writing uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of this writing include traders in Pasar Senen Petaling Jaya. From the results of this writing shows that the interest of traders regarding murabaha financing is still very lacking. This is due to several factors that cause the lack of interest of traders regarding murabaha financing, including: 1) The Knowledge Factor is due to the lack of knowledge of the products of BSI. This information helps traders to evaluate products and understand the benefits of murabaha products. traders. 2) Location Factors By choosing a strategic place that can and carry out the goals of the business objectives to achieve the desired profit and and broad marketing 3) Social Factors which are very significant in the formation and development of a person's interest 4) Promotion Factors one way of communication between the company and the wider community with the aim of introducing goods and services to the public.